Synthesis, characterization and cytotoxic activity of naturally isolated naringin-metal complexes - Emad M. Atta; Khaled H. Hegab; Ahmed A.M. Abdelgawad; Abdelghany A. Youssef (Elsevier, 2019)
High-purity naringin was isolated from the fruit peels of Citrus maxima and characterized by various spectroscopic methods like UV and NMR. The isolated compound ligand (HL) was used as ligand-metal complexes synthesis after using Ag (I), Y (III) and Ru (III) metals. These ligand-metal complexes were characterized by elemental analysis, FT-IR, UV-VIS, TGA, molar conductance and magnetic properties. Cytotoxic activity of the isolated naringin and its metal complexes were investigated against two human cancer cell lines namely, white breast Adenocarcinoma (MCF7) and Lung carcinoma (A549) using cell viability assay. Transition metal increased the cytotoxic activity of naringin when they were conjugated. LC50 of Ag ligand complex demonstrated strong cytotoxicity against MCF-7 and A549 cell line that was found higher active more than three and four times the strength, respectively when compared to LC50 of Adriamycin. While LC50 of Adriamycin compound was slightly more active only about 30% and twice the strength of the Ru ligand complex against MCF-7 and A549 cell line, respectively. Keywords: Naringin (HL), Isolation, Citrus maxima, Ag(I), Y(III) and Ru (III) ligand complexes, Anticancer